Neuropilin-2 promotes growth and progression of papillary thyroid cancer cells. Issue 5 (October 2020) - Lee, Geonho; Kang, Yea Eun; Oh, Chan; Liu, Lihua; Jin, Yanli; Lim, Mi Ae; Won, Ho-Ryun; Chang, Jae Won; Koo, Bon Seok
Abstract: Objective: Neuropilin-2 (NRP2) is a coreceptor of vascular endothelial growth factor-C/D (VEGF-C/D) and plays the important role in the development of lymphatic endothelial cells, as well as neuronal development. NRP2 is known to affect aggressiveness by increasing expression in various human cancers, but the role of NRP2 in thyroid cancer is not fully understood. The purpose of this study was to investigate the NRP2 expression and its role in regulating the tumor aggressiveness in the papillary thyroid carcinoma (PTC). Methods: The NRP2 expression and its clinicopathologic correlation to PTC was determined using the data from the 262 PTC patients at a tertiary referral medical center and The Cancer Genome Atlas (TCGA) database. The potential role of NRP2 in modulating tumor growth, invasion, and metastasis in PTC was examined by using small interfering RNA (siRNA)-mediated knockdown of NRP2. Results: High expression of NRP2 was significantly associated with capsular invasion, lymphovascular invasion, lymph node metastasis, 5 or more metastatic lymph nodes, and recurrence in PTC patients. In TCGA data, the higher NRP2 expression group was significantly associated with extrathyroid extension, lymph node metastasis, and BRAF V600E mutation. The siRNA mediated knockdown of NRP2 in the PTC cells reduced the cell proliferation, migration and invasion. We also have confirmed that NRP2 knockdown suppressed epithelial-mesenchymal transition (EMT) by regulating AKT and ERK phosphorylation signaling pathways. Conclusion: Our results suggest that NRP2 regulates tumor progression in PTC and may act as a predictive factor for aggressiveness of PTC.